Conscious Immersion and the Metamodern: A Critical Analysis of the Immersive Nature of Contemporary Metafiction - Wisher, Emma Lauren (2022)
This thesis exemplifies the immersive nature of twenty-first century metafiction and examines the applicability of the emergent cultural ideology metamodernism through a critical analysis of Gilbert Adair’s And Then There Was No One, Ben Lerner’s 10:04 and David Mitchell’s Cloud Atlas, as well as through creative practice with my novel Papercut. Papercut relates the story of Eve, a conflicted woman whose life becomes monotonous and restricted following the death of her mother and the disintegration of her relationship with her fiancé Nathan, causing her to devolve rapidly from her vibrant former self. Eve’s life begins to change, however, when her estranged brother Jay and his new girlfriend Morgan visit for the week, not just because they encourage Eve to reconsider who she wants to be, but because Morgan reveals the existence of a book called Rewritten, of which its plotlines and characters share unnerving similarities with Eve’s life. Eve commences an investigation of Rewritten and its author Jessica Eden in an attempt to comprehend the book’s origin and significance, only for her life, and the lives of those around her, to begin to replicate those of the characters in Eden’s novel, causing the distinction between reality and fiction to become increasingly blurred.